IDEA ORIGINS OF FORMATION OF ALISHER NAVOI'S PHILOSOPHICAL WORLD VIEW (British Journal of Global Ecology and Sustainable Development, 2023)
This article, based on the latest achievements of Navoi studies, examines the formation of the philosophical worldview of Alisher Navoi, the ideological sources that had a key influence on the formation of his mystical (Sufi) teachings. It is known that the formation of the worldview of Alisher Navoi was influenced by many thinkers such as Nizami Ganjavi, Amir Khosrov Dehlavi, Abdurakhman Jami. Many works of Alisher Navoi are considered and, based on the analysis, it is clarified that the theological works of the great thinker, first of all, "Khamsat-ulmutahayyirin" (Five of astonishment), "Nasaim ul-muhabbat" (Venues of love...) and many others, contain aspects which are associated with tasawwuf (Sufism).